A Novel SNCA A30G Mutation Causes Familial Parkinsonʼs Disease. Issue 7 (22nd February 2021) - Liu, Hui; Koros, Christos; Strohäker, Timo; Schulte, Claudia; Bozi, Maria; Varvaresos, Stefanos; Ibáñez de Opakua, Alain; Simitsi, Athina Maria; Bougea, Anastasia; Voumvourakis, Konstantinos; Maniati, Matina; Papageorgiou, Sokratis G.; et al.
ABSTRACT: Background: The SNCA gene encoding α‐synuclein (αSyn) is the first gene identified to cause autosomal‐dominant Parkinsonʼs disease (PD). Objective: We report the identification of a novel heterozygous A30G mutation of the SNCA gene in familial PD and describe clinical features of affected patients, genetic findings, and functional consequences. Methods: Whole exome sequencing was performed in the discovery family proband. Restriction digestion with Bbvl was used to screen SNCA A30G in two validation cohorts. The Greek cohort included 177 familial PD probands, 109 sporadic PD cases, and 377 neurologically healthy controls. The German cohort included 136 familial PD probands, 380 sporadic PD cases, and 116 neurologically healthy controls. We also conducted haplotype analysis using 13 common single nucleotide variants around A30G to determine the possibility of a founder effect for A30G. We then used biophysical methods to characterize A30G αSyn. Results: We identified a novel SNCA A30G (GRCh37, Chr4:90756730, c.89 C>G) mutation that co‐segregated with the disease in five affected individuals of three Greek families and was absent from controls. A founder effect was strongly suggested by haplotype analysis. The A30G mutation had a local effect on the intrinsically disordered structure of αSyn, slightly perturbed membrane binding, and promoted fibril formation. Conclusion: Based on the identification of A30G co‐segregating with the disease in three families, the absence of the mutation in controls and population databases, and the observed functional effects, we propose SNCA A30G as a novel causative mutation for familial PD. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society